Overcoming Target Driven Fratricide for T Cell Therapy - Breman, Eytan; Demoulin, Benjamin; Agaugué, Sophie; Mauën, Sebastien; Michaux, Alexandre; Springuel, Lorraine; Houssa, Julien; Huberty, Fanny; Jacques-Hespel, Céline; Marchand, Céline; Marijsse, Jérôme; Nguyen, Thuy; et al. (Frontiers in Immunology, 2018)
Chimeric Antigen Receptor (CAR) T cells expressing the fusion of the NKG2D protein with CD3ζ (NKG2D-CAR T Cells) acquire a specificity for stress-induced ligands expressed on hematological and solid cancers. However, these stress ligands are also transiently expressed by activated T cells implying that NKG2D-based T cells may undergo self-killing (fratricide) during 24 cell manufacturing or during the freeze thaw cycle prior to infusion in patients. To avoid target-driven fratricide and enable the production of NKG2D-CAR T cells for clinical application, two distinct approaches were investigated. The first focused upon the inclusion of a Phosphoinositol-3-Kinase inhibitor (LY294002) into the production process. A second strategy involved the inclusion of antibody blockade of NKG2D itself. Both processes impacted T cell fratricide, albeit at different levels with the antibody process being the most effective in terms of cell yield. While both approaches generated comparable NKG2D-CAR T cells, there were subtle differences, for example in differentiation status, that were fine-tuned through the phasing of the inhibitor and antibody during culture in order to generate a highly potent NKG2D-CAR T cell product. By means of targeted inhibition of NKG2D expression or generic inhibition of enzyme function, target-driven CAR T fratricide can be overcome. These strategies have been incorporated into on-going clinical trials to enable a highly efficient and reproducible manufacturing process for NKG2D-CAR T cells.